PWWP2A binds distinct chromatin moieties and interacts with an MTA1-specific core NuRD complex - Stephanie Link; Ramona M. M. Spitzer; Maryam Sana; Mario Torrado; Moritz C. Völker-Albert; Eva C. Keilhauer; Thomas Burgold; Sebastian Pünzeler; Jason K. K. Low; Ida Lindström; Andrea Nist; Catherine Regnard; et al. (Nature Communications, 2018)
PWWP2A is a chromatin-binding transcriptional regulator that mediates mitosis-progression. Here, the authors provide evidence that PWWP2A directly interacts with H2A.Z nucleosomes, DNA and H3K36me3, binds to an MTA1-specific subcomplex of the NuRD complex (M1HR) and promotes changes to histone acetylation.